Effect Of Low Doses of Acetylsalicylic Acid (ASA) On the Histopathological Features of Fibroblasts in The Amniotic Membrane - Mourisa, Cut; Suryani, Des (Universitas Muhammadiyah Sumatera Utara, 2024)
Abstract: Acetylsalicylic acid (ASA) is a drug with several indications such as analgesic, antipyretic, and antithrombotic/antiplatelet. ASA is efficacious as antithrombotic at low doses and used for thrombosis therapy in stroke, antiphospholipid syndrome (APS), pre-eclampsia and eclampsia. However, the administration of ASA made pharmacokinetic interactions that cause a vitamin C deficiency condition. This study aims to determine the effect of low doses of Acetylsalicylic acid (ASA) on the histopathological appearance of fibroblasts on fetal membranes. This study used a cross-sectional design using 54 paraffin membrane blocks as samples processed into histopathological preparations. The case group received low-dose ASA and the control group did not receive low-dose ASA. Histopathological preparations were observed using a microscope to see images / count the number of fibroblast cells. The results showed that there were significant differences between the number of fibroblasts in the case group and the control group with p = 0.001 or p 0.05